Berat Badan, Feed Convertion Ratio (Fcr), Dan Berat Jaringan Adiposa Pada Tikus Hiperkolesterolemia Dengan Diet Beras Hitam - Ria Dwi Wahyu Nastiti; Nurhidajah Nurhidajah; muhammad yusuf (Universitas Muhammadiyah Semarang, 2020)
Hypercholesterolemia is a high cholesterol level in the blood and can occur if cholesterol levels in the blood exceed the normal limit, this is caused by high levels of LDL (Low Density Lipoprotein) and low levels of HDL (High Density Lipoprotein). The general objective of this study is to determine the effect of black rice diet on changes in body weight, Feed Convertion Ratio (FCR), and Adipose Tissue in Sprague Dawlay Rat as a Hypercholesterolemia. This study was in vivo experimental in animals Sprague Dawlay rats with research design posttest control group design which used 4 groups of mice weighing 175-200 grams. The research group consisted of control (-), control (+), medicine, and black rice. The results showed that mice with black rice diet lost weight, Feed Convertion Ratio (FCR), and weight of adipose tissue from the control group (+). Statistical tests show that there is a significant effect between the treatment of black rice on body weight, Feed Convertion Ratio (FCR), and weight of adipose tissue. It was concluded that feed with the addition of black rice was able to decrease weight, Feed Convertion Ratio (FCR), and weight of adipose tissue significantly in hypercholesterolemia rats.